2012
DOI: 10.1007/s11033-012-1456-8
|View full text |Cite
|
Sign up to set email alerts
|

Inter and intra-ethnic differences in the distribution of the molecular variants of TPMT, UGT1A1 and MDR1 genes in the South Indian population

Abstract: Molecular variants of polymorphic drug metabolizing enzymes and drug transporters are attributed to differences in individual's therapeutic response and drug toxicity in different populations. We sought to determine the genotype and allele frequencies of polymorphisms for major phase II drug-metabolizing enzymes (TPMT, UGT1A1) and drug transporter (MDR1) in South Indians. Allelic variants of TPMT (*2,*3A,*3B,*3C & *8), UGT1A1 (TA)6>7 and MDR1 (2677G>T/A & 3435C>T) were evaluated in 450-608 healthy South Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
3
12
1
3
Order By: Relevance
“…This is the only silent polymorphism identified that might influence P-gp expression in different human tissues in different races [11]. Based on the origin and genetic nature, Indians are grouped into (i) the Indo-Aryan present in North India and (ii) the Dravidian are predominantly in south India [12]. Both origins are genetically dissimilarities for centuries.…”
Section: Ganesan Et Almentioning
confidence: 99%
“…This is the only silent polymorphism identified that might influence P-gp expression in different human tissues in different races [11]. Based on the origin and genetic nature, Indians are grouped into (i) the Indo-Aryan present in North India and (ii) the Dravidian are predominantly in south India [12]. Both origins are genetically dissimilarities for centuries.…”
Section: Ganesan Et Almentioning
confidence: 99%
“…The genetic polymorphisms of TPMT [28, 29] can affect TPMT activity, which directly regulates the formation of 6-MMPNs and subsequently influences the 6-TGNs concentration. However, in some recently published articles, no correlation among TPMT activity, 6-TGNs levels and 6-MMPNs levels was observed [30].…”
Section: Discussionmentioning
confidence: 99%
“…Though a number of studies [7][8][9][10][11][12][13][14] are available on polymorphism of TPMT gene, data on liver transplant patients are scarce from India. Hence A prospective observational study was conducted on LT patients admitted to the department of gastrointestinal surgery, Amrita Institute of Medical Sciences and Research Centre Kochi, India during 1 the objective of our study was to assess the bone marrow toxicity induced by azathioprine immunosuppressive therapy and to identify any correlation with TPMT mutation and myelosuppression in LT patients receiving azathioprine.…”
Section: Fig 1: Metabolism Pathway Of Azathioprinementioning
confidence: 99%